MANAJEMEN PUBLIC RELATION INDUSTRI WISATA BUDAYA DI SUMENEP SAAT PANDEMI - Bagus Cahyo Shah Adhi Pradana; Bagoes Soenarjanto; Mohammad Insan Romadhan (Metacommunication: Journal of Communication Studies, 2022)
ABSTRACT  The Covid-19 pandemic has caused the tourism sector to experience major problems. The call for social restrictions and the prohibition of crowding has caused various cases of a drastic decline in the number of tourists, including in Sumenep Madura. A place that relies on tourism as one of the leading sectors has experienced paralysis in various kinds of tourism actors, including cultural tourism industry players. Overcoming these problems requires public relations management in order to survive during the pandemic. The public relations management process which consists of four steps involving problem identification, planning, communication action, and evaluation is a step that is often taken by public relations in solving a problem. Based on that, the formulation of the problem taken is how is the management of public relations for the cultural tourism industry players in Sumenep during the pandemic. The research approach uses a qualitative case study method. Data collection techniques using interviews, observation, and documentation. The determination of the informants was carried out by purposive sampling, namely the actors of the cultural tourism industry in Sumenep. The data analysis technique uses three lines of data analysis, namely data reduction, data presentation, and verification of conclusion drawing. The results of the study show that the use of research tools is not optimal by using only informal interviews and a little media research and not using surveys to find broader problems. In addition, the planning that is made is not yet mature, with many activities being carried out spontaneously. And there are no indicators in determining the success of the activities carried out as a basis for evaluation Keywords: Public Relations Management, Tourism, Cultural Tourism Actors© 2020 MetaCommunication; Journal Of Communication Studies